2013
DOI: 10.1111/anec.12105
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Low Vitamin D to Nonvalvular Persistent Atrial Fibrillation in Chinese Patients

Abstract: Low vitamin D levels are associated with AF. It may be involved in its development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 23 publications
3
53
2
2
Order By: Relevance
“…Five studies 16,17,19,20,22 with OR/HR values were obtained in which vitamin D levels were analyzed as a categorical variable; 8 studies 16 -23 in which vitamin D levels were analyzed as a continuous variable had been included in a separate analysis. Of the 8 included studies, 5 of them 16,17,19,20,22 analyzed vitamin D levels as both a categorical variable and continuous variable. Intriguingly, 1 study showed inconsistent results between categorical variable and continuous variable analyses, 19 and 1 study reported 2 separate results.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies 16,17,19,20,22 with OR/HR values were obtained in which vitamin D levels were analyzed as a categorical variable; 8 studies 16 -23 in which vitamin D levels were analyzed as a continuous variable had been included in a separate analysis. Of the 8 included studies, 5 of them 16,17,19,20,22 analyzed vitamin D levels as both a categorical variable and continuous variable. Intriguingly, 1 study showed inconsistent results between categorical variable and continuous variable analyses, 19 and 1 study reported 2 separate results.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Cox proportional hazards model, vitamin D was not observed to be associated with the development of AF [22]. Another study that included patients with non-valvular persistent AF, but no other cardiovascular disease, reported that a low vitamin D level was associated with AF [16]. Another previous study that included 102 patients with non-valvular chronic AF without any other cardiovascular disease has found an association between non-valvular AF and vitamin D deficiency [23].…”
Section: Discussionmentioning
confidence: 97%
“…A review reported that patients with HF had a vitamin D level 34% lower than that in healthy controls [14]. The relationship between the vitamin D level and AF has been analyzed in only a small number of studies, and the findings have been inconsistent [15][16]; however, to the best of our knowledge no study on the relationship between the vitamin D level and AF in patients with HF has been published. As such, the present study aimed to evaluate the relationship between vitamin D deficiency and AF in patients with chronic HF.…”
mentioning
confidence: 99%
“…Only articles that studied the relationship between vitamin D and AF were included in our review. Our search of the literature identified one experimental study [16] and five observational studies [17][18][19][20][21] that specifically investigated the relationship between vitamin D and AF (Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…Chen et al [21] found 25(OH)D levels to be significantly lower in patients with persistent non-valvular AF than in age matched controls in sinus rhythm (18.5 ± 10.3 vs. 21.4 ± 10.7 ng/ml, p b 0.05). Low serum 25[OH]D was associated with increased high sensitivity Creactive protein levels, supporting the hypothesis that inflammation may be linked to AF.…”
Section: No Association Was Found Between 25[oh]d Levels and Af In Thmentioning
confidence: 95%